Analisis Perlakuan Akuntansi Pendanaan Mudharabah Dalam Kaitannya Dengan PSAK 105 pada PT. Bank Jabar Banten Syariah - Annaria Magdalena Marpaung; Siti Ita Rosita (Jurnal Ilmiah Akuntansi dan Manajemen Ranggagading, 2012)
Existence of Syariah Bangking to be especially beneficial amid the unstable economic conditions after the global crisis. Where the Syariah Bangking largely able to demonstrate the existence of national economic growth. Regulators see it as BI (Bank Indonesia) continues its efforts to encourage the growth of Syariah Banking to Syariah Bangking can further contribute to the national economy. This study aimed to analyze how the accounting treatment funding at a Banking Mudharabah Syariah. Note that funding is one source Mudharabah third party funds. Analyzes were conducted to determine and assess whether in practice these deals are done related to funding in accordance with the principle of Mudharabah Syariah is PASK Syariah . DSN MUI fatwa, and policies set by BI. Authors doing research at PT. Bank Jabar Banten Syariah Bogor Branch office located at Simpang Warung Jambu No.9-10 Jl. Raya Bogor Pajajaran 21. From the results of research conducted at PT. Bank Jabar Banten Syariah Bogor Branch offerings indicates that a transaction is derived from the products offered funding mudharabah basically become a major revenue source third party funding, which if it is observed by the bank management will greatly assist the growth of Banks in the future in an effort to increase in revenue. But the main concern is how the accounting treatment in the financial statements, in order to fulfill the terms and conditions apply. In general PT. Bank Jabar Banten Syariah Bogor Branch has implemented the provisions applicable to the products run on Syariah. The analysis in this study indicate that PT. Bank Jabar Banten Syariah Branches Bogor have been recorded and reported financing transactions Mudharabah accordance with applicable regulations, namely PASK No.105. Therefore, encouraged to PT. Bank Jabar Banten Syariah should always follow the development of Islamic Financial Accounting Standards, DSN MUI fatwa related to financing transactions Mudharabah